New or rare data on chromosome numbers and karyomorphology of some taxa in the subgenus Seriphidium (Bess.) Rouy. (Artemisia, Asteraceae) in Turkey - Tabur, Selma; Kursat, Murat; Oney, Signem; Ozmen, Serkan; Civelek, Semsettin (Firenze Univ Press, 2014)
Subgenus Seriphidium is one of the least karyologically studied groups in genus Artemisia. In this work, chromosome number and karyotypes of six taxa belonging to Seriphidium subgenus of genus Artemisia were investigated as detailed. Both chromosome number and karyological data of all taxa studied here were the first records from Turkey. Two of the taxa are new records to science (A. spicigera K. Koch. var. vanensis Kursat & Civelek var. nova and A. taurica Willd. var. pendulosa Kursat & Civelek var. nova) and another is a new record for the flora of Turkey (A. sieberi Bess. subsp. sieberi). All of the taxa studied except for A. spicigera K. Koch. var. spicigera were polyploid. Hypo-aneuploidy was observed in one taxon, A. santonicum L. subsp. santonicum with chromosome number 2n = 6x = 52. In addition, the simultaneous existence of B chromosome and aneusomy was recorded for A. taurica Willd. var. taurica, 2n = 4x = 36 + 0, 4B; 37 + 3, 4B.
Keywords: aneusomy; B-chromosome; hypo-aneuploidy; karyotype; Seriphidium